2011
DOI: 10.1016/j.ajpath.2011.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of DISC Formation and TNFR1 Translocation to Mitochondria in TNF-α–Treated Hepatocytes

Abstract: Tumor necrosis factor receptor 1 (TNFR1) activation in hepatocytes can trigger apoptotic or inflammatory signaling. The factors that determine which signaling pathway dominates are not clear and are thought to relate to the efficiency of death-inducing signaling complex (DISC) formation. However, the steps involved in DISC formation in hepatocytes are poorly understood. In characterizing DISC formation within cultured hepatocytes, we demonstrated that TNF-␣ exposure leads to the rapid formation of a DISC invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…We previously showed that mitotically arrested cells have increased cell surface expression of TNFR1 (18). Increased TNF-TNFR1 interactions at the cell surface (or following TNF internalization) may increase the formation of death-inducing signaling complex and caspase-8 activation (51,52), which has been observed in arrested cells. Interestingly, AK301 was the most potent TNF-sensitizing agent tested in these studies, relative to other well studied microtubule inhibitors (colchicine, nocodazole, and vincristine).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that mitotically arrested cells have increased cell surface expression of TNFR1 (18). Increased TNF-TNFR1 interactions at the cell surface (or following TNF internalization) may increase the formation of death-inducing signaling complex and caspase-8 activation (51,52), which has been observed in arrested cells. Interestingly, AK301 was the most potent TNF-sensitizing agent tested in these studies, relative to other well studied microtubule inhibitors (colchicine, nocodazole, and vincristine).…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence Staining and Confocal Microscopy on Liver Sections-Livers were fixed in 2% paraformaldehyde, and the previously described standardized protocol for cryopreservation was performed (7). Livers were sectioned in a cryostat and stained as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Ledgerwood et al (29) used immunoelectron microscopy and Western blotting techniques to demonstrate that TNF is delivered to mitochondria where it interacts with a 60-kDa protein in the inner mitochondrial membrane. Recently, Eum et al (22) reported that TNF treatment of hepatocytes induces the appearance of TNFR1 and caspase 8, but not TRADD, in mitochondria. Consistent with these observations, the current work found the expression of TNFR1, caspase 8, and BID in the mitochondria of RAW 264.7, but not IC21, macrophages (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TNF induces mtROS, and TNF is delivered to mitochondria where binding proteins have been documented (22,29). Mitochondria from RAW 264.7, but not IC21, macrophages express TNFR1 (detected by a TNFR1 25-kDa C terminus peptide Ab) (Fig.…”
Section: Tnfr1/phox Interaction Is Associated With Diminished Mtros Pmentioning
confidence: 99%
See 1 more Smart Citation